trigonometry

how do i simplify (secx - cosx) / sinx?

i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx)

and then i changed sec x to 1/ cosx so that i had

((1/cosx)/ sinx) - (cos x / sinx)

after that i get stuck

  1. 👍 0
  2. 👎 0
  3. 👁 504
asked by v
  1. sec x = 1 / cos x

    sec x - cos x = 1 / cos x - cos x =

    1 / cos x - cos ^ 2 x / cos x = ( 1 - cos ^ 2 x ) / cos x

    ________________________________________

    Remark :

    1 - cos ^ 2 x = sin ^ 2 x

    _______________________________________

    1 / cos x - cos ^ 2 x / cos x = ( 1 - cos ^ 2 x ) / cos x = sin ^ 2 x / cos x


    ( sec x - cos x ) / sin x = ( sin ^ 2 x / cos x ) / sin x =

    sin ^ 2 x / ( sin x * cos x ) =

    sin x * sin x / ( sin x * cos x ) =

    sin x / cos x = tan x


    ( sec x / sin x ) - ( cos x / sin x ) = tan x

    1. 👍 1
    2. 👎 0
    posted by Bosnian

Respond to this Question

First Name

Your Response

Similar Questions

  1. Pre-Calc

    Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 -

    asked by Dave on January 2, 2007
  2. Simplifying with Trigonometry Identities

    Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each

    asked by amanda on March 7, 2007
  3. Calculus 2 Trigonometric Substitution

    I'm working this problem: ∫ [1-tan^2 (x)] / [sec^2 (x)] dx ∫(1/secx)-[(sin^2x/cos^2x)/(1/cosx) ∫cosx-sinx(sinx/cosx) ∫cosx-∫sin^2(x)/cosx sinx-∫(1-cos^2(x))/cosx sinx-∫(1/cosx)-cosx sinx-∫secx-∫cosx

    asked by Janice on March 15, 2015
  4. Precalculus/Trig

    I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't

    asked by Heather on August 15, 2014
  5. precal

    1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a

    asked by olivia on March 25, 2012
  6. Pre-Calculus

    How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(secx-tan)=(secx+tanx)^2 I tried starting from the left on both problems, but am stuck. like I said before, change everything into sines and cosines. for the first

    asked by Corin on May 4, 2007
  7. Gr 11 Functions

    Simplify (1+tanx)^2 The answer is (1-sinx)(1+sinx) Here's what I do: 1 + 2tanx + tan^2x When I simplify it becomes 1 + 2(sinx/cosx) + (1+secx)(1-secx) What am I doing wrong?

    asked by AlphaPrimes on May 2, 2016
  8. drwls

    My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to

    asked by Jon on March 7, 2008
  9. Trigonometry Check

    Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] =

    asked by Anonymous on February 20, 2012
  10. Pre Calculus

    Having trouble verifying this identity... cscxtanx + secx= 2cosx This is what I've been trying (1/sinx)(sinx/cosx) + secx = 2cosx (1/cosx)+(1/cosx) = 2 cosx 2 secx = 2cosx that's what i ended up with, but i know it's now right.

    asked by Alex on April 11, 2013

More Similar Questions